Buenos Aires metropolitan area green spaces system development, challanges and opportunities - Pérez, Damián A.; Hidde, Gisela I.; Micou, Valeria M.; Simonyan, Martin F.; Perreta del Missier, Vanina G. (4D Journal of Landscape Architecture and Garden Art, 2018)
Buenos Aires metropolitan area, as other global megacities, deal with complex planning and governance problems regarding the allocation and conservation of green space. During the second half of the XX century regional plans have considered the allocation of land for green space with dissimilar success. The preservation of green space is mainly threatened by weak governance, discontinuous planning policies, and unplanned informal development. Flood-prone areas and public land have kept their structure mostly because of its relative unsuitability for development; however, over the years, these remnants of open space have been shrinking constantly. Even though the urban area expansion is constant there are still some areas that could be considered as part of a future city’s green space system. The lower delta of the Parana river in the north-west and the coast of Rio de la Plata in the south-east of the city are promising areas but face big threats because of unplanned development or new urbanization and infrastructure projects.